POW+TREE STRATEGY ON HIGH SCHOOL STUDENTS’ WRITING ACHIEVEMENT IN MUNTOK, INDONESIA - Riany Mutmainah; Annisa Astrid; Winny Agustia Riznanda (Premise: Journal of English Education and Applied Linguistics, 2026)
The purpose of this study was to determine whether: (1) there was a significant improvement in the twelfth-grade students' writing achievement before and after treatment using the POW+TREE strategy, and (2) there was a significant difference between students who were taught using the POW+TREE strategy and students who did not at SMAN 1 Muntok, Bangka Barat. The writing test was administered using a pre- and post-test in a quasi-experimental design. An experimental group was taught using POW+TREE, and a control group was taught through a strategy that is usually used by the teacher. The results showed a substantial improvement in the writing ability of the experimental group students after the implementation of the POW+TREE strategy, as well as significant differences between the experimental and control groups. This study also fills an empirical gap, as previous research on POW+TREE has focused mainly on lower grade levels under Curriculum 2013, whereas this study examines twelfth-grade students in the Merdeka Curriculum context. The findings of this research indicated that the POW+TREE strategy is effective in helping students improve their more structured, organized, and communicative writing skills.